P105 Lung cancer staging – are we getting it right?. (15th November 2016) - Ibrahim, J; Mukhopadhyay, A; Lostarakos, V; Mahmood, A; Khan, S; Maddekar, N; Bikmalla, S; Lea, A; Satur, C; Abid, Q; Ghosh, S; Haris, M
Abstract : Introduction: Despite significant advances in the diagnostic and staging modalities, lung cancer survival remains poor. Accurate staging and stratification of lung cancer is imperative to appropriate management. We reviewed the accuracy of staging in all patients who underwent surgical resection for confirmed or suspected lung cancer. Methods: Retrospective study of consecutive surgical resections over 5 year period between January 2010 and December 2014; patients referred from other hospitals were excluded due to lack of pre-operative staging information. Surgical database and pre-operative diagnostic information was reviewed. Results: 298 patients underwent surgical resection, mean age 68 years (range 26–91), male 150 (50%). All patients had staging CT. 108 (36%) had EBUS/Bronchoscopy, 9 (3%) had pleural aspiration, 39 (13%) had CT guided lung biopsy, 8 (3%) other tissue sampling* (pelvic lesion, subcutaneous lymph node, previous wedge biopsy & exploratory thoracotomy). Mean time from staging CT to resection was 47 days. 48 (16%) had histo-cytological confirmation of lung cancer prior to resection. 248 (83%) were primary lung, 17 (6%) metastatic lung tumours from other primaries (breast, colorectal, bladder and renal), 2 (1%) lymphoma and 31 (10%) benign. Of the 248 patients with lung primary (see Figure 1 ), pre-operative staging was available in 234; 60/234 (26%) were down staged on post-operative staging, 54 (23%)) upstaged and 120 (51%) showed concordance. Conclusion: Despite the use of combined pre-operative assessment, staging accuracy was only 51% and histo-cytological confirmation of lung cancer was only available in a small number of patients. Every effort should be made by the multidisciplinary team to accurately stage lung cancer to guide appropriate therapeutic intervention.